Three new species of the Homoneura (Homoneura) henanensis species group (Diptera, Lauxaniidae), with a key to Chinese species - Wang, Junchao; Gao, Caixia; Yang, Ding (Zootaxa, 2012)
The following three species of the nominal subgenus of Homoneura van der Wulp from China are described as new to science:H. (H.) beijingensis sp. nov. H. (H.) caoi sp. nov. and H. (H.) kuankuoshuiensis sp. nov. A key to the species of the H. (H.) henanensis species group from China is presented.